“Cogito ergo sum et sentio ergo sum”: Philosophical Reflections on Contemporary Education - Dolska, Olga; Godz, Nataliіa (Studia Warmińskie, 2021)
The focus of today’s discussion is on education and the application of online learning. The ideology of the Enlightenment emphasized the mind and required the development of self-knowledge and self-awareness of the individual, starting from Cogito as a central position in educational practice. Online education has provided an opportunity to look at the transformations in it from broader perspectives and to speak about the urgent necessity of the adjustment of the classical theory of education or even significant changes in it. A new paradigm of education (paradigm of understanding) is impossible without taking into account the heuristics of the corporeal and the harmonious combination of philosophical positions – Cogito ergo sum and Scentio ergo sum. This is a fundamental position for understanding the rationality of the Post-Enlightenment. The new pedagogical theories are based on a foundation that takes into account not only the traditional Cogito (I think), but also the conceptual and philosophical foundations of the theory of bodily cognition. Contexts of modern scientific research on human evolution allow us to put forward the thesis of the urgency of forming a very complex methodology, which should be based on knowledge of human morphology and take into account the constant process of coevolution of body, environment and mind (consciousness), because human perceptions and actions are improved due to their harmonious interaction. This thesis is reinforced by the development of HCI (Human-Computer Interaction Programs), because they focus on the introduction of those sensations into cyberspace, which can only be bodily heuristics, that can improve and make educational practices more successful and methodologically diverse.